Comparison of genetic services with and without genetic registers: access and attitudes to genetic counselling services among relatives of genetic clinic patients. Issue 12 (1st December 2002) - Kerzin-Storrar, L; Wright, C; Williamson, P R; Fryer, A; Njindou, A; Quarrell, O; Donnai, D; Craufurd, D
Abstract : The pedigrees of 192 subjects at risk of Duchenne or Becker muscular dystrophy, myotonic dystrophy, or balanced chromosome translocations attending three regional genetic clinics were inspected to identify relatives who were themselves at high risk of these disorders. Of the 342 relatives eligible for inclusion, 43% (63/147) of the register relatives and 26% (50/195) of the non-register relatives had had contact with the clinical genetic services, a significant difference (p<0.02). Relatives from families with muscular dystrophy were significantly more likely to have been in contact with genetic services than those from BT families. Fifty-two relatives were interviewed about their experience and attitudes regarding genetic counselling. Almost all regarded knowledge about the family genetic disorder as helpful, and only one thought it unacceptable for relatives to be informed that they are at risk; 94% thought it was acceptable for this information to come from family members, 92% from general practitioners, and 90% from the clinical genetic service. A majority of relatives (53%) thought it was the family's responsibility to pass on genetic risk information, but 22% said the genetic service should be responsible and 18% thought it should be the GP. These data, together with the findings from the study of probands attending genetic clinics for these disorders, indicate that the genetic register approach incorporating long term follow up and a proactive approach to genetic counselling is acceptable to the families concerned and improves access to genetic services for at risk relatives.